EVALUASI FORUM MERDEKA BARAT 9 SEBAGAI WUJUD RELASI MEDIA DENGAN PEMERINTAH - Rachmawati, Farikha; Kriyantono, Rachmat (Universitas Merdeka Malang, 2019)
Abstract This study discusses the positives and negatives received by the journalist Forum Merdeka Barat 9 (FMB9) as an evaluation of the government public relations program. Government Public Relations initiated FMB9 to get access for the media to get information related to the government agenda. In addition, the presence of FMB9 represented a single government narrative in accordance with Presidential Instruction No. 9 of 2015. Forum Merdeka Barat 9 is one of the flagship programs that form the Directorate General of Information and Communication of the Ministry of Communication and Information Technology (Dirjen IKP Kemenkominfo) which consists of media discussions or press conferences as the government's main news source. This study used quantitative methods and data collection techniques, namely Forum Group Discussion (FGD) for 30 FMB9â€™s journalists. Informants consisted of journalists from printed media, television and online media in three discussion sessions. Aspects that include: information completeness, focus, right time, easy access, ease of information, media discussion, free media permission, and information clarity, will then be used to explore quantitative analysis to see FMB9's effectiveness and to remove programs in this forum is activated. The results of this study reveal the Benefits of FMB9 for journalists after the arrival of FMB9. Keywords: Merdeka Barat 9 Forum, Media Relations, Communication Evaluation, Government Public RelationsDOI :Â https://doi.org/10.26905/nomosleca.v5i1.2749